2018
DOI: 10.1093/hmg/ddx442
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher disease iPSC-derived osteoblasts have developmental and lysosomal defects that impair bone matrix deposition

Abstract: Gaucher disease (GD) is caused by bi-allelic mutations in GBA1, the gene that encodes acid β-glucocerebrosidase (GCase). Individuals affected by GD have hematologic, visceral and bone abnormalities, and in severe cases there is also neurodegeneration. To shed light on the mechanisms by which mutant GBA1 causes bone disease, we examined the ability of human induced pluripotent stem cells (iPSC) derived from patients with Types 1, 2 and 3 GD, to differentiate to osteoblasts and carry out bone deposition. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 79 publications
3
45
1
3
Order By: Relevance
“…Several groups decided to use human induced Pluripotent Stem Cells (iPSC)‐derived osteoblasts to address the unknown of the bone pathology in GD. The main study so far is the one recently published by Ricardo Feldman's group . They showed that GD iPSC‐derived osteoblasts had developmental and lysosomal defects that impaired bone matrix deposition.…”
Section: Gaucher Diseasementioning
confidence: 99%
“…Several groups decided to use human induced Pluripotent Stem Cells (iPSC)‐derived osteoblasts to address the unknown of the bone pathology in GD. The main study so far is the one recently published by Ricardo Feldman's group . They showed that GD iPSC‐derived osteoblasts had developmental and lysosomal defects that impaired bone matrix deposition.…”
Section: Gaucher Diseasementioning
confidence: 99%
“…Specifically, evidence that reprogrammed cells can be differentiated into osteoblasts [ 54 , 55 , 56 ], chondrocytes [ 57 , 58 , 59 , 60 ], myoblasts [ 61 ], nucleus pulposus cells [ 47 , 48 , 49 ] and tenocytes [ 62 ] has recently impacted musculoskeletal research and changed orthopedic medicine. Nevertheless, the use of iPSCs for studying the wide variety of musculoskeletal conditions has been explored to a limited extent ( Table 1 ) in comparison with conditions affecting nervous or cardiac pathologies, even when investigating genetic disorders where symptoms affect several organs or systems [ 63 , 64 , 65 , 66 ].…”
Section: Disease Modelingmentioning
confidence: 99%
“…Panicker et al [ 66 ] using iPSCs shed light on the mechanisms that could lead to GD. This disease is developed due to alterations in the gene that encodes acid β-glucocerebrosidase and causes bone abnormalities in patients.…”
Section: Disease Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…As with many lysosomal storage disorders, patients with Gaucher disease exhibit skeletal dysplasias and low bone mass (41). Gaucher disease iPSC-derived osteoblasts display defective osteoblast differentiation and mineralization caused by defects in Wnt/-catenin signaling, an effect that is reversed by treatment with recombinant GCase (42). Accordingly, we speculated that this suppression of -catenin signaling and osteoblast differentiation and function may be a consequence of defects in sclerostin control, as sclerostin inhibits both of these processes.…”
Section: Disrupted Lysosomal Function In Gaucher Disease Leads To Sclmentioning
confidence: 99%